The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00381-021-05216-6
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculosubgaleal shunt and neuroendoscopic lavage: refining the treatment algorithm of neonatal post-hemorrhagic hydrocephalus

Abstract: Background The optimal management of neonatal post-hemorrhagic hydrocephalus (PHH) is still debated, though several treatment options have been proposed. In the last years, ventriculosubgaleal shunt (VSgS) and neuroendosdcopic lavage (NEL) have been proposed to overcome the drawbacks of more traditional options, such as external ventricular drainage and ventricular access device. Methods We retrospectively reviewed neonates affected by PHH treated at our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(43 reference statements)
0
14
0
1
Order By: Relevance
“…Components of the protocol that were not mandated or specified, such as type of temporising device, reflect areas where there is limited evidence to suggest that these factors have any influence on outcome, highlighting areas of practice that would benefit from future research should NEL be validated and implemented as routine management for PHVD. Interestingly, despite variation in the published practice of NEL [ 1 , 4 6 , 8 , 9 ], all participating paediatric neurosurgeons in this consensus ultimately agreed that NEL should be performed as an adjunct and not replacement to the procedure of temporising device insertion, particularly when NEL is being performed at the time of development of PHVD (when the ventricular index crosses the 97th centile + 4 mm). In this consensus process, the timing of NEL was agreed as when the ventricular index crosses the 97th centile + 4 mm; however, there is recognised variation in practice documented in literature with regard to the timing of NEL [ 4 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Components of the protocol that were not mandated or specified, such as type of temporising device, reflect areas where there is limited evidence to suggest that these factors have any influence on outcome, highlighting areas of practice that would benefit from future research should NEL be validated and implemented as routine management for PHVD. Interestingly, despite variation in the published practice of NEL [ 1 , 4 6 , 8 , 9 ], all participating paediatric neurosurgeons in this consensus ultimately agreed that NEL should be performed as an adjunct and not replacement to the procedure of temporising device insertion, particularly when NEL is being performed at the time of development of PHVD (when the ventricular index crosses the 97th centile + 4 mm). In this consensus process, the timing of NEL was agreed as when the ventricular index crosses the 97th centile + 4 mm; however, there is recognised variation in practice documented in literature with regard to the timing of NEL [ 4 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that VSgS and NEL are two effective treatment options. Both procedures should be part of the neurosurgical armamentarium to deal with PHH [17]. Honeyman et al confirmed that NEL is a safe and potentially efficacious treatment for neonatal IVH [18].…”
Section: Discussionmentioning
confidence: 99%
“…Components of the protocol that were not mandated or specified, such as type of temporising device, reflect areas where there is limited evidence to suggest that these factors have any influence on outcome, highlighting areas of practice that would benefit from future research should NEL be validated and implemented as routine management for PHVD. Interestingly, despite variation in the published practice of NEL [1, 35, 7, 8], all participating paediatric neurosurgeons in this consensus ultimately agreed that NEL should be performed as an adjunct and not replacement to the procedure of temporizing device insertion, particularly when NEL is being performed at the time of development of PHVD (when the ventricular index crosses the 97 th centile + 4mm).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have suggested that NEL may be effective at reducing shunt dependence and allowing good motor and cognitive outcomes [3][4][5][6][7]. However, there is considerable variation in NEL practice and currently there is no randomised trial evidence supporting the use of NEL [8].…”
Section: Introductionmentioning
confidence: 99%